Hubungan Perkembangan Wisata terhadap Ekonomi Wilayah di Gunungkidul Selatan - GILANG ADINUGROHO (P4W LPPM IPB, 2017)
Disparity is still a common problem in regional development, including at Gunung Kidul Regency. Rapid development is taking place at Wonosari, the capital region of Gunungkidul Regency, while other districts are lagged behind, especially the southern part of Gunungkidul which are underdeveloped and having low economic contribution. Tourism is seen as one of the alternatives to increase economic development since the increase of the number of tourists visits. The aims of this study was to identify the tourism sector development in southern Gunungkidul and to analyze its impact towards the district’s economy. The method used in this study is quantitative using paired sample t test and Pearson correlation for data analysis. The data showed that there was an increasing trend in the number of tourist visit during 2007 to 2013 eventhough with a lack of tourism infrastructures, especially in Panggang, Saptosari and Girisubo subdistrict. The data also showed that there was an increasing of Gross Regional Domestic Product (GRDP) in trade and entertainment sector between 2007 and 2013. The result of comparative analysis showed that there are significant differences of GRDP of these two sectors between 2007 and 2013. The correlation analysis showed that there was no significant relationship between the number of tourist visits and the extent of the sector in GRDP. High number of visits is not necessarily related to the increasing level of GRDP.